A clinical study of pediatric hypomelanotic dermatoses at tertiary care center - Babu, Aneeha Ramesh; Prasad, Anupama Manohar (Indian Journal of Child Health, 2019)
Background: Hypopigmentary and depigmentary lesions are frequently encountered in pediatric age group which can be alarming and distressing to parents. They may be insignificant or denote an underlying multisystem disorder. Hence, a thorough medical history, clinical, Wood’s lamp examination, and an interdisciplinary consultation may aid in the correct diagnosis of these dermatoses. Objectives: The objectives of the study were to study the various hypopigmentary and depigmentary dermatoses in children attending the outpatient department of a tertiary care center in South India. Materials and Methods: A descriptive study was conducted at the outpatient department of dermatology at the tertiary care center of South India, where 121 patients aged between 0 and 18 years presenting with hypopigmentary and depigmentary skin lesions from August 2018 to August 2019 were included in the study irrespective of gender. A detailed history, clinical examination, and basic investigations were done. Results: Out of 121 children included in our study, 67 (55.37%) were girls and 54 (44.62%) were boys. The mean age of the study group was 9.8 years. The most common dermatosis observed was pityriasis alba (28.9%), followed by primary disorders of hypopigmentation (vitiligo, lichen striatus, nevus depigmentosus, nevus anemicus, halo nevus, hypomelanosis of Ito, progressive macular hypomelanosis, and blaschkoid dermatitis), post-inflammatory hypopigmentation (19.8%), pityriasis versicolor (8.2%), Hansen’s disease (3.3%), and morphea (2.4%). Conclusion: The most common hypomelanotic dermatosis noted in the present study was pityriasis alba followed by primary disorders of hypopigmentation and depigmentation. Most of the dermatoses were either self-limiting or benign in nature and required only reassurance and managed with only medical line of management. These diseases may be the reason for undue concern and anxiety in parents; hence, a thorough evaluation and management of these dermatoses are necessary.